P PENGARUH FOCUS GROUP DISCUSSION (FGD) TERHADAP PENGERAPAN 3M (MENCUCI TANGAN, MEMAKAI MASKER DAN MENJAGA JARAK) - lukman harun (Journal of Nursing Invention, 2022)
Background: At the beginning of 2020, the world was shocked by the outbreak of a new virus, namely the new type of coronavirus (SARS-CoV-2) and the disease is called Coronavirus disease 2019 (COVID-19). It is known, the origin of this virus came from Wuhan, China. The entry of the corona virus in Indonesia has had a major impact on people's lives, the spread of the Corona virus or COVID-19 in Indonesia must be prevented as much as possible. One of the main ways is to apply a disciplined lifestyle. So, with that we must always take the 3M steps, namely wearing masks, washing hands, maintaining distance, as an effort to prevent and break the chain of transmission of COVID-19. One of the methods of conducting health education is with a focus group discussion (FGD). Objective: To determine the effect of focus group discussions (FGD) on the implementation of 3M (Washing Hands, Wearing Masks and Keeping Distance) Method: The design of this research is a quasi-experimental with a population of people living in the village of Pemurus Banjarmasin. The research sample was 30 respondents. The research design was one group pre-test and post-test. The independent variable Focus Group Discussion (FGD) and the dependent variable 3M implementation were analyzed using the Wilcoxon test. The results showed that the Wilcoxon statistical test results were significant, namely 0.000 which is smaller than 0.05 as a predetermined level (p < ) and it can be stated that there is a very significant influence between the FGD and the application of 3M in Pemurus Dalam Village, Banjarmasin. Conclusion: The results of this study were obtained if there was a very significant influence between the FGD and the application of 3M in Pemurus Dalam Village, Banjarmasin